A Physiological Study of Hypothyroid Patients in the City of Samawa - Abbas, Hawraa Hamza (American Journal of Biology and Natural Sciences, 2025)
Thyroid disease can be specified as the second most common endocrine condition affecting several body systems. The purpose of the presented study has been investigating hypothyroidism effects on the fasting blood sugar level (FBS), hemoglobin level (Hb), and the prevalence of hypertension, anemia, and diabetes in such two groups. Ten healthy people, both female and male, between the ages of 30 and 65, served as controls in the study, along with 40 patients who had previously been diagnosed with hypothyroidism (40 cases). Significant differences in Hb levels have been found between the two groups, with the control group having the highest levels and the hypothyroidism group having the lowest. In comparison to the control group, the hypothyroidism group saw a significantly increased frequency of anemia. Additionally, the hypothyroidism group had a much higher diastolic blood pressure. Furthermore, in comparison with the control group, the hypothyroidism group experienced a significantly increased frequency of hypertension. The FBS levels between the two groups have shown significant differences as well. In the hypothyroidism group in comparison with the control group, the frequency regarding diabetes has been significantly higher. We advise all hypothyroid patients to undergo routine assessments for potential changes in their cardiovascular, hematological, biochemical, and dental health in light of the information acquired.